The Role of the PI3K Signaling Pathway in CD4+ T Cell Differentiation and Function - Handi, Jonathan; Patterson, Scott J.; Levings, Megan (Frontiers in Immunology, 2012)
The relative activity of regulatory versus conventional CD4+ T cells ultimately maintains the delicate balance between immune tolerance and inflammation. At the molecular level, the activity of phosphatidylinositol 3-kinase (PI3K) and its downstream positive and negative regulators has a major role in controlling the balance between immune regulation and activation of different subsets of effector CD4+ T cells. In contrast to effector T cells which require activation of the PI3K to differentiate and mediate their effector function, regulatory T cells rely on minimal activation of this pathway to develop and maintain their characteristic phenotype, function and metabolic state. In this review, we discuss the role of the PI3K signalling pathway in CD4+ T cell differentiation and function, and focus on how modulation of this pathway in T cells can alter the outcome of an immune response, ultimately tipping the balance between tolerance and inflammation.